Computer-Based Analysis of News Values: A Case Study on National Day Reporting. (26th April 2021) - Bednarek, Monika; Caple, Helen; Huan, Changpeng
ABSTRACT: This article uses Discursive News Values Analysis (DNVA) in a case study of national day reporting, focussing on the discursive dimension of news values. The study crosses disciplinary boundaries by bringing together linguistics and journalism studies. More specifically, it examines reporting about "Australia Day"—the official national day of Australia, which is set on a date that is becoming increasingly controversial, as it marks the beginning of colonisation. Importantly, the article utilises digital technologies (computer-based text analysis and visualisation of word co-occurrence) to apply and test these methods for the analysis of news values in English-language reporting. The study findings will thus have broader implications for journalism research. These methods (e.g., word frequency, collocation, concordancing) have been used in corpus linguistics and other areas of the digital humanities, including in the analysis of journalistic texts, but most often with a focus on language practices or discourses. Our study demonstrates that journalism research can profit from the use of free and user-friendly tools such as the ones that are applied in this study. Beyond this methodological innovation, the study will contribute new insights to research on news values in national day reporting.